The characteristics of protein-glutaminase from an isolated Chryseobacterium cucumeris strain and its deamidation application - Qu, Ruidan; Dai, Tian; Wu, Jiajing; Tian, Aitian; Zhang, Yanfang; Kang, Li; Ouyang, Wei; Jin, Congli; Niu, Jinjin; Li, Zhen; Chang, Zhongyi; Jiang, Deming; et al. (Frontiers in Microbiology, 2022)
Protein-glutaminase (PG), a deamidation enzyme commercially derived from Chryseobacterium proteolyticum, is used to improve the solubility and other functional properties of food proteins. In this study, a new PG-producing strain Chryseobacterium cucumeris ZYF120413-7, was isolated from soil, and it had a high PG yield and a short culture time. It gave the maximum PG activity with 0.557 U/mL on Cbz-Gln-Gly after 12h of culture, indicating that it was more suitable for PG production. The enzyme activity recovery and purification fold were 32.95% and 161.95-fold, respectively, with a specific activity of 27.37 U/mg. The PG was a pre-pro-protein with a 16 amino acids putative signal peptide, a pro-PG of 118 amino acids, and a mature PG of 185 amino acids. The amino acid sequence identity of PG from strain ZYF120413-7 was 74% and 45%, respectively, to that of PG from 9670T and BH-PG. The optimum reaction pH and temperature of PG was 6 and 60 ℃, respectively. Enzyme activity was inhibited by Cu2+. The optimum PG substrate was Cbz-Gln-Gly, and the Km and Vmax values was 1.68 mM and 1.41 μM mg protein-1 min-1, respectively. Degree of deamidation (DD) of soy protein isolate (SPI) treated by purified PG was 40.75 % within the first 2 h and 52.35% after 18 h. These results demonstrated that the PG from C. cucumeris ZYF120413-7 was a promising protein-deamidating enzyme for improving the functionality of food proteins.